An unexpected surprise: rare association of neuroendocrine tumours in inflammatory bowel disease. Issue 9 (19th September 2020) - Pat, Jackson J; Iqbal, Muhammad Rafaih; Wright, Christopher
Abstract: Neuroendocrine neoplasms are rare malignancies, more so when cancerous metastasis occurs without a known primary source. Here we discuss a case of an ulcerative colitis sufferer, 43-year-old lady presented with what was thought to be a flare up. Situation deteriorated and was taken to theatre to find a significantly ischaemic colon, secondary to extensive venous thrombosis. The ischaemic bowel was resected alongside with what was thought to be a large, reactive lymph node. To our surprise, the resected lymph node returned with evidence of neuroendocrine neoplastic metastasis. Multiple laboratory and imaging investigations were performed in hope to identify the primary source. A second metastatic lymph node was identified and subsequently resected but the primary remains elusive. Currently, there are no visible evidences of active disease.